Continuing Medical Education, Maintenance of Certification, and Physician Reentry - Luchtefeld, Martin; Kerwel, Therese G. (Clinics in Colon and Rectal Surgery, 2012)
Continuing medical education serves a central role in the licensure and certification for practicing physicians. This chapter explores the different modalities that constitute CME along with their effectiveness, including simulation and best education practices. The evolution to maintenance of certification and the requirements for both the American Board of Surgery and the American Board of Colon and Rectal Surgery are delineated. Further progress in the education of practicing surgeons is evidenced through the introduction of laparoscopic colectomy and the improvements made from the introduction of laparoscopic cholecystectomy. Finally, reentry of physicians into practice following a voluntary leave of absence, a new and challenging issue for surgeons, is also discussed.
Keywords: continuing medical education; maintenance of certification; physician reentry